SURVEY BALANCE ABILITY IN STROKE PATIENTS AT THONG NHAT GENERAL HOSPITAL IN DONGNAI PROVINCE (Vietnam Journal of Community Medicine, 2026)
Objective: To survey some related factors to balance ability in stroke patients at the Department of Neurology, Thong Nhat Dong Nai General Hospital in 2024.Method: The study design used a cross-sectional descriptive study method. Including 97 patients who met the selection criteria for the study. The sampling method was convenient.Results: Of the 97 patients participating in the study, the average age was 59.97 ± 10.98, with the highest age group being 56-65 (27.8%). When assessed by the Berg scale, the Berg scale scores in women were higher than in men, respectively, at 31.50 ± 9.54 and 29.29 ± 10.44, the rate of patients at medium and very high risk of falling was 57.8% and 27.8%, respectively. The study showed that there are several factors related to balance ability in order: obesity, stroke type, hypertension and osteoarthritis, muscle tone, muscle strength, ROM significantly affecting the patient's balance function.Conclusion: The survey results showed that there are many factors related to balance function in post-stroke patients. Therefore, a good management plan to prevent high risk of falls for patients right in the hospital room is proposed, and a suitable physical therapy plan for each patient.
Keywords: balance, stroke, relationship